USES AND GRATIFICATIONS THEORY AND DIGITAL MEDIA USE: THE TEST OF EMOTIONAL FACTORS - Luo, Margaret Meiling (PEOPLE: International Journal of Social Sciences, 2020)
We study online digital media use by adoption uses and gratifications theory and technology acceptance model. With an online survey, we collected data from 73 college students who enrolled in an IT course and analyze the data by using stepwise multiple regressions and semi-structured analysis. Through principal component analysis and multiple regression analysis we identify major motivations of online newspaper use. The purpose of the analysis is to understand whether affective constructs–entertainment, perceived enjoyment, and perceived playfulness–are different. The results suggest that entertainment is the most important use motivation of digital media use. Interestingly, information motivation is not the most salient motivation, assumed to be the major reason for media use. From the results we can see that the motivation of digital media is different from traditional media. Along with the theorization of the technology acceptance model, we also identify that perceived enjoyment and entertainment motivation are different constructs. The structured relationship of motivations and use intention is also tested.